2020
DOI: 10.1177/0954410020910883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the novel rib layouts on the tip leakage flow pattern and heat transfer performance of turbine blade

Abstract: The steady simulation with flow field and heat transfer performance for different rib layouts is investigated. By referring the GE-E3 turbine blade tip (Case 1) profile as a prototype model, four kinds of rib layouts of full rib structure (Case 2), half rib structure connected with suction side (Case 3), half rib structure connected with pressure side (Case 4), and half rib structure in the rear squealer cavity (Case 5) was designed. The availability of k-ω turbulence model was validated through comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…The rib number and installation angle have significant influences on the aero-thermal performance of squealer tip. Then, Du et al 24 and Jiang et al 25 numerically investigated the aero-thermal performance of the multi-cavity squealer tip in a turbine stage. Their results suggested that the rib location and geometry significantly affect the aero-thermal performance of squealer tip.…”
Section: Introductionmentioning
confidence: 99%
“…The rib number and installation angle have significant influences on the aero-thermal performance of squealer tip. Then, Du et al 24 and Jiang et al 25 numerically investigated the aero-thermal performance of the multi-cavity squealer tip in a turbine stage. Their results suggested that the rib location and geometry significantly affect the aero-thermal performance of squealer tip.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In the early stage, researchers studied the effect of single side squealer tip on TLF through experiments and numerical methods and found that the suction side squealer tip has a better blocking effect on the TLF. 10,11 Then, more and more researchers focused on the geometric optimization of the squealer tip, such as the number and layout of rims, [12][13][14] cutback configurations, 15,16 and the width and depth of rims. 17,18 The researchers from the von Karman Institute for Fluid Dynamics (VKI) [19][20][21] tried to optimize the squealer-like tip geometry by using the differential evolution algorithm and finally obtained the double-cavity tip configuration with great aerodynamic and thermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Du et al 20 added riblet design perpendicular to tip camber line to effectively segment high heat transfer stripe, thus improving overall heat transfer effect of blade tip. Jiang et al 21 continued to optimize rib size inside blade tip and further reduced tip heat transfer coefficient by reducing rib length in tip trailing region. Park et al 22,23 also studied blade tip rib design on tip aerothermal performance.…”
Section: Introductionmentioning
confidence: 99%